Synthesis, Characterization and Reactivity Studies on Mixed-Ligand Organometallic Complexes of Rhodium and Iridium with Triphenyl phosphine and Ethylene thiourea - Pandey, R.N.; Shahi, Kalpana; Pandey, Preety (Asian Journal of Chemistry, 2012)
Mixed ligand organometallic complexes of rhodium and iridium with triphenyl phosphine and ethylene thiourea have been prepared and characterized by chemical, spectroscopic (IR and electronic), molar conductivity and magnetic susceptibility measurements. Rhodium(I) complexes were iso-structural with precursors and are four co-ordinated square planar; iridium(I) complexes show square planar structure whereas iridium(III) complexes exhibit octahedral structure. The thioamide ligand behaves as neutral monodentate having bonding through thione tautomeric form.